Fabrication of fire‐response functional separators with microcapsule fire extinguishing agent for lithium‐ion battery safety. Issue 5 (3rd November 2021) - Lou, Ping; Zhang, Weixin; Han, Qigao; Tang, Shun; Tian, Jie; Li, Yan; Wu, Hao; Zhong, Yunhui; Cao, Yuan‐Cheng; Cheng, Shijie
Abstract: Fire safety issues hinder the large‐scale application of lithium‐ion batteries (LiBs). Here, a new type of fire‐response separators is prepared by loading the microcapsule fire extinguishing agent on the surface of the separator. The shell of the microcapsule will break automatically at a certain temperature and release the fire extinguishing agent when thermal runaway of LiBs occurs, which can quickly absorb heat through endothermic reaction and ensure LiBs will not burn or explode. The porosity of fire‐response separator is 53.6%, the electrolyte uptake is 132% and the ionic conductivity is 1.00 mS cm ‐1 . The initial specific capacity is 2643 mAh g ‐1 at 4°C and the capacity retention rate is 93% after 200 cycles for NCM523 battery based fire‐response separator. The temperature of LiBs based on the fire‐response separator can automatically drop to room temperature in 20 seconds, which ensures the safety of other adjacent LiBs. This work proposes a new active protection concept to solve the safety problem of LiBs. Abstract : A new type of fire‐response separators is prepared by loading the microcapsule fire extinguishing agent on the surface of the separator. The shell of the microcapsule will break automatically and release the fire extinguishing agent when thermal runaway of LiBs occurs, which can quickly absorb heat through endothermic reaction and ensure LiBs will not explode.